A emergência da governança socioambiental no mercado internacional de biocombustíveis - Perosa, Bruno Benzaquen (2012)
The decline of fossil fuels reserves and the climate change process caused by GHG emissions have placed biofuels as the main alternative energy source available for transportation uses in the next years. However, the existence of externalities and information asymmetries imposes a barrier for the development of a sustainable market for biofuels. Therefore, the design of institutions to guarantee the sustainability on the production and consumption of these products seems to be a precondition for the expansion of this market. The construction of institutions for socioenvironmental governance depends on technical, political and institutional variables. Using institutional lens, this research analyzed the factors affecting this process by considering the evidences collected from the trajectory of two sectors with similar features (organic food and timber/forest). The way national regulations, international agreements and certification schemes have evolved on these sectors show many common points with the trajectory observed on the biofuels market until present time. Among the main results, can be pointed a tendency of convergence in sustainability standards between different national regulations and private certification schemes due to network externalities, which increases the value of standards adopted by a larger network of users. European Union seems to be the most influent player due to its considerable importing capacity and the central role of sustainability on the regulations currently used on member states. On the other side, the U.S., although its huge consumption potential, tends to be play smaller influence because of the large capacity of domestic production and the important role of other strategic factors (rural development and energy security) on the design of American biofuels policies. On the private governance category, the development and expansion of certification schemes depends on technical factors, like the capacity and cost of monitoring relevant criteria, and political factors, related to the capacity to gain legitimacy of the actors coordinating each of these schemes. It can also be observed that technological and organization characteristics of the biofuels production chain plays an important role on the expansion of certification schemes, affecting both the costs of establishing a chain of custody and the capacity to coordinate sectorial initiatives to implement more sustainable production practices. This difficult can be seen on new players from Africa and Central America which aim to build a biofuels industry integrating family farming to a sustainable biofuels chain, able to comply the international sustainability standards. This research reveled the need for more analysis on the new technological paths and actors arriving on the biofuels market. Further studies considering the potential and risks of integrating public and private governance mechanisms are also necessary for the development of this and other sectors in which environmental attributes are relevant.